The freak-garde : extraordinary bodies and revolutionary art in America - Blyn, Robin (University of Minnesota Press, 2013)
Since the 1890s, American artists have employed the arts of the freak show to envision radically different ways of being. The result is a rich avant-garde tradition that critiques and challenges capitalism from within. This book traces the arts of the freak show from P. T. Barnum to Matthew Barney and demonstrates how a form of mass culture entertainment became the basis for a distinctly American avant-garde tradition.